Immune responses related to the immunogenicity and reactogenicity of COVID-19 mRNA vaccines - Matsumura, Takayuki; Takano, Tomohiro; Takahashi, Yoshimasa (International immunology, 2023)
Abstract Vaccination for the prevention of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection is considered the most promising approach to control the pandemic of coronavirus disease 2019 (COVID-19). Although various COVID-19 vaccines have been developed worldwide using several modalities, the vaccines that have shown the highest efficacy to date are mRNA vaccines. Despite their extensive usage, the mechanisms that stimulate the immune responses associated with their immunogenicity and reactogenicity remain largely unknown. In this review, we summarize and discuss current knowledge on immune responses to COVID-19 mRNA vaccines, including potential immune responses and correlating factors underlying the immunogenicity and reactogenicity of mRNA vaccines. We also describe recent trends in the optimization of lipid nanoparticles and vaccination routes. Further understanding of vaccine-elicited immune responses will guide the development of more effective and safe vaccines. The immune responses triggered by COVID-19 mRNA vaccines Graphical abstract Graphical Abstract